The analysis of prognostic factors and treatment outcomes in breast cancer patients with brain metastasis (Annals of Medical Research, 2022)
Aim: Breast cancer (BC) is among the most common causes of brain metastasis (BM). Brain metastasis leads to severe morbidity and mortality. Brain metastasis-related survival is not common despite all treatments. The aim of the present study is to compare the short-term or long-term surviving patients who underwent radiotherapy due to BM in our clinic regarding treatment modalities, and clinic-pathological characteristics as well as to investigate the factors that influence overall survival and progress for BM development.Materials and Methods: The data of 167 patients who were referred to radiotherapy due to BM were analyzed retrospectively. The patients were allocated to two groups: ones who survived less than, or more than, 14 months. The treatment, patient, and tumor characteristics were evaluated.Results: The frequencies of a better Karnofsky performance scores (p=0.001), her-2 positivity (p
Keywords: Breast cancer; brain metastasis; radiotherapy; prognosis; long survival